Synthesis and modification of silver-seeded PVC for use as anti-adherent materials to prevent ventilator-associated pneumonia - Jia Li; Matthew Wylie; Colin P McCoy (University of Huddersfield Press, 2022)
In this research, silver-seeded PVC was synthesised and modified to combat ventilator-associated pneumonia by preventing bacterial adherence. The silver-seeded PVC was synthesised by in situ deposition of silver particles, and the silver-seeded PVC was further modified by reacting with 3,3,4,4,5,5,6,6,7,7,8,8,9,9,10,10,10-heptadecafluoro-1-decanethiol to create a superhydrophobic surface with static water contact angle more than 150°. The silver-coated PVC and superhydrophobic silver-coated PVC both exhibited excellent anti-adherent activity against MRSA and Pseudomonas aeruginosa.